Concentrations and exposure risks of per- and polyfluoroalkyl substances in human milk from Southern China during the first 400 days of lactation - Meng-Tao Yang; Fei Yang; Qiu-Ye Lan; Si-Yu Huang; Xiao-Yan Chen; Ying-Zhen Qiu; Hui-Lian Zhu (Ecotoxicology and Environmental Safety)
Per- and polyfluoroalkyl substances (PFASs) pose significant health risks, particularly for infants who are highly susceptible during early life. Although several studies have reported PFASs concentrations and exposure risks in human milk in China, they typically cover only up to 3 months postpartum, failing to align with the WHO recommendation of continued breastfeeding to 2 years of age. Therefore, this study aimed to address this gap by investigating the concentrations and exposure risks of legacy and emerging PFASs in human milk collected during the first 400 days postpartum from Southern China. We detected all the target 23 PFASs compounds, with 22 PFASs found in more than half of the samples. The median concentration of total PFASs in human milk was 151 ng/L, with PFOA, PFOS, 6:2 Cl-PFESA, and 8:2 Cl-PFESA being the most abundant. Total PFASs concentration peaked within the first 45 days postpartum (median, 154 ng/L), significantly higher than that at 200 −240 days (median, 145 ng/L) and 300 −400 days postpartum (median, 148 ng/L). PFBA, PFOA, PFNA, ADONA and PFOS also exhibited similar lactation patterns. Additionally, we calculated the estimated daily intakes (EDIs) of total PFASs for infants by multiplying their concentration in human milk by daily milk consumption, and dividing by body weight. The median EDIs of PFASs were 19.0, 10.2, and 9.03 ng/kg bw/d at 0 −45 days, 200 −240 days, and 300 −400 days postpartum, respectively. The corresponding median hazard quotients of PFASs for infants were 11.2, 5.43, and 5.23, respectively. These findings suggest persistent risks of PFASs exposure for infants through human milk during the first 400 days postpartum. However, breastfeeding remains the optimal choice due to its significant health benefits. It is crucial to reduce human milk PFASs concentrations by minimizing dietary and environmental exposures among lactating women.